Performance analysis based on DDoS attack at MAC layer in WLAN / Zati Bayani Harun - Harun, Zati Bayani (2019)
Wireless Local Area Network (WLAN) is an advance of technology that brought important changes to human life. Now, it is an integral part of everyday life, creature increasingly affordable and easier to build. But WLAN suffer from several security threats and one of that is Distributed Denial of Service (DDoS) attack which is jamming attack. Almost 81% of jamming attacks are initiated at the MAC layer due to the nature of wireless networks that lead to this project. Main objectives of this paper are to configure jamming attack at MAC layer in WLAN and to evaluate the performance of WLAN by using three types of metrices which is Bit Error Rate (BER), Throughput and Signal to Noise Ratio (SNR). For this purpose, jammer sending the maximum packets to the network to avoid legitimate nodes from sending their packets through wireless environment. OPNET Modeler 14.5 is used to configure and Microsoft Excel 2016 to analyze the performance of the network. A comparison of two scenarios which is network without attack and network with attack was conducted. It concluded that Throughput is a best metric to detect the attack compared to others.